Sistem Informasi Rumah Sakit Umum Daerah Kota Padang Panjang Berbasis PHP dan Database MySQL - Fadillah Akbar; Aulia Fitrul Hadi (Universitas Putra Indonesia YPTK Padang, 2020)
Nowadays computers can almost be found in every office, company, school, or even household. The development of computer technology is very rapid, especially in the field of software, making computers become more user friendly and has made it a necessity for certain circles, for example businesses. Computers are no longer only used as a substitute for messpot or arithmetic, but are now also widely used in helping important decision making. As a result, the information stored requires security that can protect against unauthorized access. And with the development of this technology, this research has developed a system for health services in the Padang Panjang City General Hospital. The methods used for this application are Data Flow Diagrams and Entity Relationship Diagrams. And for the programming language using PHP while for the database using MySQL. The information system that was built was able to provide information convenience for admins, nurses, and directors to do their jobs. Helping administrators, nurses, and directors to find information related to public health services. This information system provides information about services provided by the hospital staff. In providing services to the community.